A critical study of assessments made during a trial interview situation - Pons, A L (Rhodes University, Faculty of Humanities, Department of Psychology, 1951)
At the end of 1948 the National Institute for Personnel Research (N.I.P.R.) organised a series of testing procedures for the selection of administrative trainees for a large industrial organisation. The fruitful results obtained by the British War Office and the Civil Service selection Boards in the application of approved techniques for similar purposes supplied the basis on which the battery of tests was constructed. While having regard for this established approach as well as the controlling influence imposed by the stipulations of the contract, the N.I.P.R. was able to devise a battery which provided scope for its specific interest in research. Intro., p. 1.
Keywords: Interviewing